Green Synthesis of Chitosan‐Stabilized Copper Nanoparticles. Issue 28 (24th July 2013) - Tokarek, Katarzyna; Hueso, Jose L; Kuśtrowski, Piotr; Stochel, Grażyna; Kyzioł, Agnieszka
Abstract: The synthesis of stable copper nanoparticles (CuNPs) has been carried out in the presence of green chemicals such as chitosan, sodium phosphinate, and ascorbic acid. The colloidal stability of the copper nanoparticles has been evaluated for a period of one month. No further aggregation or significant changes in the overall oxidation state of the resulting nanoparticles has been detected, thereby proving the viability of this one‐step synthesis method. In addition, different control experiments have shown that the presence of the three reactants is necessary to obtain stable copper nanoparticles for periods of time longer than one week. The use of chitosan as a natural polymer with stabilizing properties enables its application in the biomedical field owing to its demonstrated biocompatibility, biodegradability, and lack of toxicity. Sodium phosphinate acts as a co‐reducing agent and the ascorbic acid prevents the formation of copper sub‐oxides owing to its antioxidant properties. Abstract : Chitosan is presented as an environmentally friendly biopolymer indispensable to yield long‐term stabilized metallic CuNPs. The present synthesis represents a simple, convenient, cost‐effective, and greener alternative to previous methods in which organic solvents, elevated temperatures, and inert atmospheres are required.